FENOMENA KEBEBASAN BEREKSPRESI DI INSTAGRAM - Hardina, Andhika Febi (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2021)
ABSTRACT Instagram is one of the platforms that is widely used by the public for freedom of expression. However, the term freedom itself gets a lot of perceptions so that many issues are against ethics and norms. Some elements cover themselves in a word